A scalable optical meta-surface glazing design for agricultural greenhouses - Lakshminarayanan, Venkatasubramanian; Ranjbar, Mostafa; Ibrahim, Khalifa Aliyu; Luo, Zhenhua (IOP Publishing, 2024)
Optical meta-surfaces allow controllable reflection and transmission spectra in both optical and infrared regions. In this study, we explore their potential in enhancing the performance of low-emission glazing designed for improved energy efficiency, for agricultural greenhouses in cold climates. The low-emission glazing employs thin film optics to retain heat by allowing solar radiation while reflecting radiation emitted by room-temperature objects. The incorporation of metamaterials that can be scalably manufactured and designed for capturing solar energy in the mid-infrared spectrum, offers an opportunity to further enhance the glazing's energy efficiency. Based on existing literature, the finite difference time domain (FDTD) method and the transfer matrix method are utilised to propose a metamaterial structure, with spherical silver nanoparticles and thin-films. We compare the performance of this proposed design against existing materials. The outcome of this study offers insights into the potential of metamaterials in optimizing the energy efficiency of cold-climate agricultural greenhouses.
Keywords: FDTD (finite difference time domain); thin films; optical metamaterials; low-emissivity; plasmonic; nanoparticle; glazing